Product Layout Design Analysis at Nurasiah Minimarket With FP-Growth Algorithm - Eka Bagus Sugara; Adli Abdillah Nababan (Putaka Timur Publisher, 2021)
With today's technological advances, the need for accurate information is needed in everyday life. Computerized information systems make it easier for organizations to collect and store various data in a large-scale database. One of the fields that are engaged in marketing companies that are currently developing with technology media is the field of commerce or more precisely, minimarkets. Minimarkets currently process a lot of data every day starting from purchase data, sales data, and transaction data, with the advancement of Information Technology, business people must be able to develop strategies to face competition with similar business actors so that the profits from each transaction increase. The layout of the goods is needed by the seller because if the goods are not neatly arranged according to the type of product, the goods will make it difficult for buyers to find the goods to be purchased, thereby reducing the number of goods to be purchased by consumers. Therefore, a system is needed to build an appropriate item layout pattern to increase sales transactions at minimarkets. in it, there is a procedure called Market Basket Analysis to seek knowledge in the form of relationships between items in a data set and display it in the form of patterns that explain consumer habits in shopping. The application of data mining with association functions can help determine the appropriate pattern in sales so that it can help Nurasiah Minimarket in making sales.